Sentence Patterns And Their Translations Analysis Found In The Novel “The Wonderful Wizard Of Oz” - I Made juliarta (International Journal of Linguistics and Discourse Analytics, 2022)
This study entitled “Sentence Patterns and their Translations Analysis Found in the Novel The Wonderful Wizard of Oz”. This study aims to: (i) analyze the tree diagram structure of sentence patterns found in the in the Novel The Wonderful of Oz, (ii) analyze the types of translation shifts of sentence patterns in the translation process found in the data source. This study analyzed Sentence Patterns and their Translations Analysis Found in the data source. The analysis applied the theory of sentence patterns proposed by Quirk and Greenbaum and the theory of translations shift by Catford. The process of collecting data was conducted by reading novel entitled “The Wonderful Wizard of Oz” to understand the story and observe the data of sentence patterns that were taken from the story. In the method of collecting data, the data source was read to get complex sentences and simple sentence found in the data source. This study found that there are six sentence patterns that are translated by applying unit shift. This study applied the theory related to syntax, types of sentences, sentence pattern, tree diagram, and relevant previous studies. Syntax is called as one of the branches that focus on the sentence structure. This research study applied theory of translation shift proposed by Catford. Based on the results of analysis, there were two types of translation shifts found in the novel. Those are 6 data that were translated in unit shifts, 1 data translated in level shift and 4 data that were translated in structure shifts